2000
DOI: 10.1159/000024859
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation for People

Abstract: The developing trend that Building Regulations in the future will be applied to buildings in use rather than to their design intent on paper has many important implications. It will lead to pressure testing of new buildings to ensure air tightness, low energy bills and the associated absence of draughts. Importantly, it means that for the first time, the ventilation air will enter the building through the air inlet ductwork. This offers the designers the opportunity to control the indoor environment to create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The range of variations, as summarised in Table 3, was determined based on a review of the design values adopted by existing office buildings in Hong Kong. 25 There are altogether 17 cases (cases [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] included in the parametric study; and the design values of the original case (base case) are also shown in Table 3. …”
Section: Studied Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…The range of variations, as summarised in Table 3, was determined based on a review of the design values adopted by existing office buildings in Hong Kong. 25 There are altogether 17 cases (cases [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] included in the parametric study; and the design values of the original case (base case) are also shown in Table 3. …”
Section: Studied Parametersmentioning
confidence: 99%
“…Consequently, SHR, Q L and Q T are affected. Table 4 also summarises the annualised Q S , Q L , Q T and SHR of the base case and the additional 17 cases (cases [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Influential Load Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are various literature providing reviews and assessment of the effectiveness of various types of ventilations for various types of buildings [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. To satisfy the requirement of the building regulations (or building codes) of various countries, mechanical ventilation with heat recovery is required and there are various reports regarding the effectiveness of such system in terms of improving IAQ of homes [63][64][65] and offices [66][67][68][69][70]. There is also an increase use of demand control ventilation [71][72][73][74], higher efficiency of filters [75][76][77] and air-cleaning systems [78À81].…”
Section: Introductionmentioning
confidence: 99%